Pediatrics Infected with COVID-19: A Case Series Study on Pediatrics Hospitalized in a Referral Pediatric Hospital - Houman Hashemian; Saeid Sadat Mansouri; Hamid Reza Badeli; Ebrahim Esmaili; Majid Asgharzadeh; Tamkin Shahraki; Neda Aligoli Ghasemabadi; Reza Falahatkar; Parham Mashouf; Alireza Jafari (International Journal of Pediatrics)
Introduction. COVID-19 infection which is a novel pneumonia associated with coronavirus suddenly broke out in the world. The aim of this study is to analyze and summarize the clinical characteristics of pediatric patients who were hospitalized in a referral pediatric hospital because of COVID-19 infection. Materials and Methods. Twenty-one COVID-19 infection cases confirmed by clinical and laboratory findings who were hospitalized in our center from 20 February to 19 April 2020 were included. Demography information, clinical, laboratory, and radiological findings, and treatment strategies of patients were evaluated. Results. The mean age was 91.5±68.38 months (1-225), and there were 12 (57.1%) boys and 9 (42.9%) girls. Fever≥38°C was detected in 11 (52.4%) patients. Eleven (52.3%) patients had tachypnea, and 4 (19%) of them developed tachycardia. Nine CT scans (42.85%) demonstrated a halo sign, and patchy infiltration was seen in CT scan of 7 patients (33.33%). Furthermore, bilateral crazy-paving pattern was seen in CT scan of nine (42.85%) patients. We prescribed chloroquine in 8 (38.1%), oseltamivir in 8 (38.1%), Kaletra in 6 (28.6%), and Ribavirin in 1 (4.8%) of patients. Finally, four (19.04%) patients expired which one of them suffered from ARDS. Conclusions. We found out that boys might develop more severe cases of COVID-19, and this could be more common in school age. Manifestations might be milder than adults, and the most severe cases might be associated with underlying diseases. Also, the effectiveness of drugs in the treatment of this disease needs further study.